Las ventajas de ser un marginado - Chbosky, Stephen 1970- (Alfaguara [u.a.], 2012)
Charlie, un chico ingenuo, mordaz y solitario, acaba de empezar el instituto. Vive con sus padres, su popular hermana y un hermano mayor que está a punto de comenzar la universidad. La cosa no pinta demasiado bien el primer día de instituto cuando solo consigue hacer un amigo: un alternativo profesor de Lengua interesado en despertar el genio creativo de Charlie. - A coming of age novel about Charlie, a freshman in high school who is a wallflower, shy and introspective, and very intelligent. He deals with the usual teen problems, but also with the suicide of his best friend
This paperback ed. published 2012. Originally published in English in 1999
Keywords: High school students / Social conditions / Juvenile fiction; Teenagers / Juvenile fiction; Letters / Juvenile fiction; Bildungsromans; High school students / Social conditions / Fiction; Teenagers / Fiction; Letters / Fiction; Coming of age / Fiction; Spanish language materials; Adolescentes / Novela; Adolescentes / Novela juvenil; Männliche Jugend; Erwachsenwerden; Freundschaft; Trauerarbeit; Tod; High school; Außenseiter; Jugendbuch